REVITALISASI FILOSOFI ORNAMEN BERMOTIF MELAYU PADA DESAIN CORAK ANYAMAN GEDEBONG PISANG: KAJIAN KEARIFAN LOKAL BUDAYA MELAYU - Juliana Juliana; Hetty Zaharani (Faculty of Humanities, Universitas Jenderal Soedirman, 2019)
This article aims to revitalize the phylosophy of Malay motif ornament in the design of woven gedebong. This research uses a qualitative descriptive method with ethnographic approach. The data were collected through observation, interview and documentation. There were four motifs used to revitalize and develop philosophical of Malay culture in the design of woven gedebong, they were flora, fauna, natural and wajik motifs. Firstly, flora motifs ornaments are from lined up flower (bunga berjajar), reap flower (bunga tampuk manggis), single florets (kuntum bujang), gundur florets, cloudy florets (kuntum awan larat), eartquake motion flower (bunga gerak gempa) on the handicraft of pencil case, cake box, skewer, kleenex box. Secondly, fauna motifs ornaments are from dragon (naga-nagaan) ant (semut beriring), twinned pigeon (merpati sekawan), return home duckling (itik pulang petang) on the handicrafts of sandal, kleenex box, and hat. Thirdly, outer space buih selari on the handicraft of astray. And lastly, Wajik motif are from portion form wajik (wajik petak tabur) and similar title of princess wajik (wajik payung sekaki tajuk puteri) on the handicraft of bag and stationery box. The philosophical local wisdom values of Malay ornaments are the values of good behaviours, taqwa (faith) to Allah, harmony, wisdom, heroic, affection, fertility, self-knowing, fair, responsibility. The result showed that there are some Malay motif ornaments used to develop in the woven gedebong that can be useful to revitalize the Malay philosophical of local wisdom values.